Hubungan Efikasi Diri dengan Kecemasan Menyusun Skripsi pada Mahasiswa Keperawatan - Niken Saraswati; Meidiana Dwidiyanti; Agus Santoso; Diyan Yuli Wijayanti (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2021)
Introduction: Students who writing their thesis experience difficulties during the COVID-19 pandemic result in anxiety. The feeling can arise due to a low self-efficacy that view difficult experiences as threats and think about the possibility of failure. Previous studies show different relationship between self-efficacy and anxiety thus requires further research particularly in seeking the relationship of self-efficacy and anxiety on thesis’s writing among undergraduate nursing students.Methods: This study was a correlational study with all of undergraduate nursing students who is writing a thesis as the population. Subjects (112 students) were selected by a proportionate stratified random sampling method. Questionnaires used in this study were General Self-Efficacy Scale (GSES) and Zung Self Rating Anxiety Scale (ZSRAS). Data analysis was performed by Pearson Correlation tests.Results: Main results distinguished that there is a negative relationship between self-efficacy and anxiety of undergraduate nursing students who is writing a thesis with r = -0.445 which is indicate that the relationship between two variable is strong enough.Discussion: Students need to make a list of goals to be achieved, so they are encouraged to try to achieve these goals more. Moreover, students can conduct a variety of things to reduce their anxiety.